If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x(7 + -1y) + 4 = -4 (7 * -2x + -1y * -2x) + 4 = -4 (-14x + 2xy) + 4 = -4 Reorder the terms: 4 + -14x + 2xy = -4 Solving 4 + -14x + 2xy = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -14x + -4 + 2xy = -4 + -4 Reorder the terms: 4 + -4 + -14x + 2xy = -4 + -4 Combine like terms: 4 + -4 = 0 0 + -14x + 2xy = -4 + -4 -14x + 2xy = -4 + -4 Combine like terms: -4 + -4 = -8 -14x + 2xy = -8 Reorder the terms: 8 + -14x + 2xy = -8 + 8 Combine like terms: -8 + 8 = 0 8 + -14x + 2xy = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(4 + -7x + xy) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + -7x + xy)' equal to zero and attempt to solve: Simplifying 4 + -7x + xy = 0 Solving 4 + -7x + xy = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -7x + -4 + xy = 0 + -4 Reorder the terms: 4 + -4 + -7x + xy = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -7x + xy = 0 + -4 -7x + xy = 0 + -4 Combine like terms: 0 + -4 = -4 -7x + xy = -4 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 9+10(1+7a)= | | -3+4b= | | r=-4 | | -2x(7-y)+7=-4 | | -4(x+1)=-13-4x | | 5/6(18)+3/7(28) | | 36t=78 | | 12=8-4(n+1) | | 3(d+8)=3d | | x/3+25=33 | | 6r+4=18 | | 11-5(9x+2+4x-8)=-4(10x+42)-23 | | 5(9/25) | | 23/4k+3/4+6=64/5 | | n/7=5.55 | | 6+2a*3b-4a+5= | | 8+2(a-5)= | | -5y-10=-1-3(4y-11) | | 6-7x=10x+10 | | -3-3x=-3(x+1) | | 4(4m-5)+4=6(2m-6) | | 13=x/3+4 | | .75x+6=.66x-8 | | 3r-9=0 | | 2x+7=-53 | | 40-8x/x-5 | | 6/7(x+1)=1/21(x+2) | | 3(x-5)+5x=8(x+1) | | -9=-2--3r | | 7(-5x-2)= | | 3(y-10)+1=.25(y-8) | | -1(7-y)+4=-4 |